International surveillance study in acute spinal cord injury confirms viability of multinational clinical trials - Bourguignon, Lucie; Tong, Bobo; Geisler, Fred; Schubert, Martin; Röhrich, Frank; Saur, Marion; Weidner, Norbert; Rupp, Rüdiger; Kalke, Yorck-Bernhard B.; Abel, Rainer; Maier, Doris; Grassner, Lukas; et al. (BMC medicine, 2022)
The epidemiological international landscape of traumatic spinal cord injury (SCI) has evolved over the last decades along with given inherent differences in acute care and rehabilitation across countries and jurisdictions. However, to what extent these differences may influence neurological and functional recovery as well as the integrity of international trials is unclear. The latter also relates to historical clinical data that are exploited to inform clinical trial design and as potential comparative data.